Primero Madres: love and mothering in the educational lives of Latina/os. Issue 4 (7th June 2017) - Velazquez, Mirelsie
ABSTRACT: This article examines the historical and contemporary role of Latina madres in the educational lives of their children and communities. Latinas, in their work as mother-activists, have played critical roles in the schooling lives of their children, seeking educational equality for their communities in general, amidst the growing racial politics they contended with within US schools. I aim to examine here how these mothers challenged traditional conceptions of feminism, as they bridge a politics of motherhood and activism for survival in their everyday lives. These mothers transform their children's lives – and by extension their own lives and the lives of their community – through discourses of love that complicate traditional gender roles and forge new articulations of feminist solidarity. I utilize Chicana feminist theory to highlight the intersectionality of Latina identities to examine the quotidian struggles of women occupying multiple roles in the face of inequality in contemporary US society.